Multiple conductance classes of mouse nicotinic acetylcholine receptors expressed in Xenopus oocytes. - Kullberg, R (1990)
Acetylcholine receptor (AcChoR) subunit mRNAs transcribed from mouse BC3H-1 cDNAs were injected into Xenopus oocytes and the expressed AcChoR channels were examined by single channel recording. Injection of alpha-, beta-, gamma-, and delta-subunit mRNAs produced two predominant channel classes with conductances of approximately 50 and approximately 12 pS, while infrequent openings of approximately 25-pS channels were also observed. Injection of alpha-, beta-, and gamma-subunit mRNAs produced a single class of approximately 12-pS AcChoR channels, which resembled the smallest conductance channels present in alpha beta gamma omega-injected oocytes. Assembly of delta-less channels may thus explain the lowest conductance AcChoR channels in alpha beta gamma delta-injected oocytes and might also account for similar channels that have been observed in vertebrate skeletal muscle.